A new paradigm in management of frequent attenders to emergency departments with severe alcohol use disorder—A pilot study for assertive community treatment in Singapore - Mak, Charles Chia Meng; Mao, Desmond Ren Hao; Siddiqui, Fahad Javaid; Lim, Alex; Davamoni-Thomas, Jayson; Tang, June Peiwen; Bachik, Rozinah; Ng, Charis Wei Ling; Kandasami, Gomathinayagam; Lee, Cheng (Frontiers in Health Services, 2022)
Introduction A majority of frequent users of emergency medical services in Singapore present with alcohol-related problems. These patients are known to engage poorly with traditional addiction services and frequently attend Emergency Departments (EDs) instead, resulting in high healthcare burden. Assertive Community Treatment (ACT) is an alternative intervention to traditional addiction management. ACT involves community visits with focus on holistic care and harm-reduction. Materials and methods We conducted a prospective before-and-after cohort study at the major tertiary center for addiction disorders in Singapore. The main objective was to evaluate effectiveness of ACT in reducing alcohol-related attendances at EDs nationwide. Socio-demographics, alcohol-related ED attendances, and the Christo Inventory for Substance-misuse Services (CISS) scores were collected for the patients recruited from April 2018 to March 2019. Descriptive analyses and the Wilcoxon Signed-Rank Test were performed. Results All 14 patients were male with a mean age of 55 years. There was a significant 45.3% reduction in average alcohol-related ED attendances from 6.8 (range 3–22, median 5.5) in the pre-intervention 6-month period, to 3.7 (range 0–28, median 1.5) in the post-intervention 6-month period (Z = −2.244, p = 0.025). CISS scores showed significant improvement from a pre-intervention median of 13.5 (range 9–16) to a post-intervention median of 6.5 (range 1–10, p = 0.001), corresponding to reduction in alcohol-related problem severity. Conclusion This pilot study suggests that ACT can be effective in reducing alcohol-related ED attendances and alcohol-related problem severity in patients with AUD who frequently attend ED. A multicenter, prospective study using ACT for such patients across four hospitals in Singapore is currently underway.